2018
DOI: 10.1111/tpj.13854
|View full text |Cite
|
Sign up to set email alerts
|

FCS‐like zinc finger 6 and 10 repress SnRK1 signalling in Arabidopsis

Abstract: SNF1-related protein kinase 1 (SnRK1) is a central regulator of plant growth during energy starvation. The FCS-like zinc finger (FLZ) proteins have recently been identified as adaptor proteins which facilitate the interaction of SnRK1 with other proteins. In this study, we found that two starvation-induced FLZ genes, FLZ6 and FLZ10, work as repressors of SnRK1 signalling. The reduced expression of these genes resulted in an increase in the level of SnRK1α1, which is the major catalytic subunit of SnRK1. This l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
53
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(62 citation statements)
references
References 66 publications
9
53
0
Order By: Relevance
“…Through repression of SnRK1, FLZ6 promotes target of rapamycin or TOR signalling pathway that induces growth in favourable conditions. FLZ6 mutants show inhibition and reduced seedling growth under favourable growth conditions due to enhanced SnRK1 activity that confirms role of FLZ6 in plant growth by regulating SnRK1 signalling (Jamsheer et al , 2018). FLZ6 was found to be up-regulated under SHADE at latitude 67°2’N as compared to latitude 56°2’N, which may indicate that the trees in the northern latitudes are better adapted to shade conditions by withstanding the shade stress and continue to grow better compared to the southern populations.…”
Section: Discussionsupporting
confidence: 55%
“…Through repression of SnRK1, FLZ6 promotes target of rapamycin or TOR signalling pathway that induces growth in favourable conditions. FLZ6 mutants show inhibition and reduced seedling growth under favourable growth conditions due to enhanced SnRK1 activity that confirms role of FLZ6 in plant growth by regulating SnRK1 signalling (Jamsheer et al , 2018). FLZ6 was found to be up-regulated under SHADE at latitude 67°2’N as compared to latitude 56°2’N, which may indicate that the trees in the northern latitudes are better adapted to shade conditions by withstanding the shade stress and continue to grow better compared to the southern populations.…”
Section: Discussionsupporting
confidence: 55%
“…The in planta analysis identified that FLZ proteins interact with SnRK1 subunits in the common cytoplasmic foci indicating the formation of a complex. The colocalization analysis with a marker protein and stain in this study and a previous study identified that SnRK1-FLZ interaction colocalizes with ER, which provides clues about the biological significance of this complex (14). In most cases, these interactions were found to be located in the proximity of the nucleus suggesting that it might be the regions in ER where ribosomes are studded and mRNA translation is undergoing.…”
Section: Flz Proteins Form Snrk1 Scaffold In Land Plantssupporting
confidence: 63%
“…Functional analysis of FLZ genes identified their roles in the regulation of many SnRK1-regulated processes (11)(12)(13). Consistent with these studies, we recently identified that two members of Arabidopsis FLZ gene family work as negative regulators of SnRK1 signaling (14). Interestingly, many FLZ proteins also showed interaction with RAPTOR, which suggests that they may work as scaffolds by bringing both SnRK1 and TOR complexes in close proximity, which is required for the energy-dependent antagonistic interaction (8,10).…”
supporting
confidence: 60%
See 1 more Smart Citation
“…7 genes were found to be induced in all three data sets. Interestingly, one gene of this category named FLZ8 was found to be a member of the land plant-specific FLZ family implicated in nutrient signaling 26 . FLZ8 physically associates with SnRK1α and β subunits and RAPTOR1B subunit of TOR 27,28 .…”
Section: Data-driven Screening Identifies Potential Negative Feedbackmentioning
confidence: 99%